KNOWLEDGE MANAGEMENT SYSTEM FOR MEASURING MATURITY LEVEL OF INFORMATION TECHNOLOGY SERVICE QUALITY USING INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY (ITIL V3) FRAMEWORK (A Case Study at IBI Darmajaya Bandar Lampung) - Handayani, Retno Dwi; Aziz, RZ Abdul (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The implementation of technology information and communication is needed in the field of education and business as a tool for carrying out businesses. It changes all patterns and ways in all fields, especially in a field of businesses so that a company must use information technology in order to be a competitive organization. Information technology service quality and continuous improvements are the important factor used to encounter competitions, to improve performances, and to provide customer satisfaction. Informatics and Business Institute (IBI) Darmajaya is one of the private universities that use the information technology for academic activities. One of the information technologies used by IBI Darmajaya was the Academic Information System. This objective of this research was providing convenience for companies or colleges on IT services to measure the maturity level of the IT service quality using the Knowledge Management System-based Information Technology Infrastructure Library (ITIL) V3 framework. This system was designed to obtain online IT service rates about the information technology quality so that the current level of information technology that the current maturity and the expected maturity were known. The validity and reliability of the research instruments had already been tested using SPSS 23 so that the result of this research was the recommendations for improvements on the IT service quality for the future.Keywords: Knowledge Management System, Maturity Level, Current Maturity, Expected Maturity, Validity, Reliability, ITIL V3